PENGARUH KONSUMSI MINUMAN SEGAR BUAH Etlingera hemisphaerica (MSBE) TERHADAP KADAR GLUKOSA DARAH PADA PEKERJA TAMBANG EMAS - Sari, Fenty Fitrian; Nursa'adah, Euis; Karyadi, Bhakti; Ruyani, Aceng; Parlindungan, Deni (LP4MK STKIP PGRI Lubuklinggau, 2023)
Etlingera hemisphaerica has been used by the community for generations as medicine. E. hemisphaerica contains flavonoids, saponins, tannins which can lower blood glucose levels. This study aims to determine the effect of giving E. hemisphaerica fruit fresh drink (MSBE) on blood glucose levels. This research is a limited clinical trial with trials of measuring blood glucose levels before and after treatment. The research prospectus consisted of gold mine workers and non-workers. Data collection was carried out before and after giving MSBE for 7 days to the probandus. Based on the T test, the results obtained are t hit ˃ t tab. In 10 probandus, the average blood glucose level before treatment was 117.5 mg/dL and blood glucose level after treatment was 93.4 mg/dL. Whereas in the 5 probands of mining workers, the average blood glucose level before treatment was 133,200 mg/dL and blood glucose level after treatment was 100,400 mg/dL. In the 5 non-mining probandus, the average blood glucose level before treatment was 101,800 mg/dL and blood glucose level after treatment was 86,400 mg/dL. Based on the results of the study it was concluded that MSBE administration had the potential to reduce blood glucose levels in 10 probandus.